Caries risk assessment as an effort to prevent dental and oral health in elementary school children at Gowa Regency: Caries risk assessment sebagai upaya pencegahan kesehatan gigi dan mulut pada anak sekolah dasar di Kabupaten Gowa - Hamudeng, Adam Malik; Sugianto, Irfan; Mude, Acing Habibie; Rachmuddin, Afniati; Permatasari, Andi Sri; Jubhari, Eri Hendra (Makassar Dental Journal PDGI Makassar, 2025)
This study aims to analyze the caries risk profile using the caries risk assessment (CRA) method in children aged 6-8 years in Gowa district with a lower middle economic background. A total of 67 children participated in this study, with a distribution bet-ween male gender 24 people and female gender 43 people. CRA showed that 13.43% of children were in the low risk category, 29.85% moderate risk, and 56.72% high risk. The main risk factors that contribute to increased caries risk include frequency of consumption of sweet foods, lack of fluoride use, poor oral hygiene, and low socioeconomic status. Caries prevalence showed a positive relationship with risk category, where in the high-risk group, 70% of children had at least one tooth with active caries. These results emphasize the importance of risk-based interventions through dental health education programs, increasing access to fluoride, and other caries prevention strategies, especially in groups of children with low socioeconomic backgrounds.